2021
DOI: 10.5398/tasj.2021.44.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Pandanus conoideus Oil in Cryopreservation Diluents for Maintaining the Semen Quality of Ongole Grade Bull

Abstract: Antioxidants such as tocopherol, ß-carotene, and polyunsaturated fatty acids (PUFA) from red fruit oil of Papua may be used to protect frozen semen. The study is aimed to test the effect of red fruit oil supplementation on motility, viability, and recovery rate of frozen sperm of Ongole-grade bulls. Semen was collected twice a month from eight 4-5-year-old male Ongole grade using an artificial vagina, followed by macro- and microscopical evaluations. Collected semen was divided into four tubes and diluted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
4
0
2
Order By: Relevance
“…Progressive motility of spermatozoa is one of important factors to support the fertilization. In this study, the progressive motility of spermatozoa ranges from 60% to 70%, in accordance with reported by Widiarta et al (2019), 69%, Pause et al (2022), maximum 80%, and lower than reported by Nurcholis et al (2021), 81,1 ± 1.42%. The percentage of live spermatozoa were from 60% to 85%, slightly lower than reported by Diansyah et al (2022), 95.73 ± 2.15.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 92%
“…Progressive motility of spermatozoa is one of important factors to support the fertilization. In this study, the progressive motility of spermatozoa ranges from 60% to 70%, in accordance with reported by Widiarta et al (2019), 69%, Pause et al (2022), maximum 80%, and lower than reported by Nurcholis et al (2021), 81,1 ± 1.42%. The percentage of live spermatozoa were from 60% to 85%, slightly lower than reported by Diansyah et al (2022), 95.73 ± 2.15.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 92%
“…Semen pH is usually correlated with sperm motility, reinforced by Dhumal et al (2021) that semen pH is closely related to sperm motility. The motility and viability of fresh semen sperm typically have normal values above 70% and 80% (Nurcholis et al, 2021). The quality of fresh semen in this study complies with Indonesian national standards (SNI 4869-1:2021).…”
Section: Fresh Semen Quality Of Po Cattlesupporting
confidence: 65%
“…The fresh semen volume of PO cattle is an average of 4.7 ml -5.4 ml. Nurcholis et al (2021) volume semen sapi PO pada umur 3 tahun rata-rata 4.8 ml. Penelitian lain voleme semen sapi PO mencapai 6.1 ml (Zamuna et al, 2016).…”
Section: Fresh Semen Quality Of Po Cattleunclassified
See 1 more Smart Citation
“…Finally, the structure will be logical, concise, and grammatically accurate. Red fruit juice boasts α-tocopherol, βcarotene, oleic acid, linoleic acid, linolenic acid, vitamin C, calcium, phosphorus, and iron (Tethool et al, 2021;Nurcholisa et al, 2021). Tabatabaei et al (2011) suggest that antioxidants, including tocopherol, β-carotene, and ascorbic acid, can protect spermatozoa cells from cellular morphological damage, which can lead to abnormalities in these cells by preventing the negative effects of free radicals.…”
mentioning
confidence: 99%